2019
DOI: 10.5606/ehc.2019.66592
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid solution combining osteosynthesis and endoprosthesis for double column acetabular fractures in the elderly provide more stability with finite element model

Abstract: ÖZAmaç: Bu çalışmada yaşlılarda çift kolon kırıklarında osteosenteze (plak ve vida tespiti) kıyasla kalça artroplastisi ile desteklenen aynı yöntemin (hibrid çözüm) mekanik stabilitesi karşılaştırıldı. Hastalar ve yöntemler: Çift kolon kırıkları için geliştirilen ileri sonlu eleman pelvis modelinde mekanik araştırmalar yapıldı. İncelenen simüle edilen implant kombinasyonları şunlardı: poliaksiyel vidalı ve U plaklı, halkalı, modüler asetabüler sepet; medial horizontal (linea terminalis) ve kuadrilateral kemik … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The most frequently investigated fracture types in biomechanical tests as well as in FEA were an ACPHT fracture (biomechanical tests: 11; FEA: 3) [ 36 44 , 60 , 63 , 66 , 71 ], a posterior column/wall fracture (biomechanical tests: 9; FEA: 2) [ 52 59 , 62 , 67 ], and a transverse acetabular fracture (biomechanical tests: 7; FEA: 2) [ 28 34 , 70 ]. Other fracture types (associated both column fracture, T-shape fracture and isolated anterior column fracture) were less frequently studied in biomechanical analyses [ 35 , 45 51 , 61 , 64 , 65 , 68 70 ]. The numbers of investigated fracture types within the reported studies are demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most frequently investigated fracture types in biomechanical tests as well as in FEA were an ACPHT fracture (biomechanical tests: 11; FEA: 3) [ 36 44 , 60 , 63 , 66 , 71 ], a posterior column/wall fracture (biomechanical tests: 9; FEA: 2) [ 52 59 , 62 , 67 ], and a transverse acetabular fracture (biomechanical tests: 7; FEA: 2) [ 28 34 , 70 ]. Other fracture types (associated both column fracture, T-shape fracture and isolated anterior column fracture) were less frequently studied in biomechanical analyses [ 35 , 45 51 , 61 , 64 , 65 , 68 70 ]. The numbers of investigated fracture types within the reported studies are demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the investigated plate systems had non-locking plate-screw connections, and only a minority of the studies evaluated a locking plate system. Furthermore, seven biomechanical analyses assessed the biomechanical properties of a THA either alone or in combination with other fixation methods [ 29 , 42 , 53 , 60 , 63 , 68 ]. THAs were mostly analyzed in studies dealing with posterior wall fractures, transverse fractures and ACPHT fractures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] Finite element modeling is a well-established method to the joint contact stresses. [15,16] In the present study, we aimed to investigate the relationship between the Böhler's angle and the stresses on the calcaneus and the subtalar joint compared to the healthy model. In our FEA, we examined any correlation between the Böhler's angle, calcaneal strength, and subtalar joint stress.…”
mentioning
confidence: 99%